2020
DOI: 10.1002/lary.28785
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surgery in Rhabdomyosarcoma of the Head and Neck in Children

Abstract: Objectives Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children. The goal of this research is to analyze the role of surgery in the management of pediatric parameningeal (PM) and non‐PM head and neck RMS (HNRMS). Study Design Retrospective review. Methods Retrospective chart review of patients <20 years of age treated for HNRMS between 1970 and 2015. Clinical presentation, tumor characteristics, treatment, recurrence, follow‐up, and outcome data were collected. Results Of 97 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…However, the difference did not reach statistical significance, which may be due to the small patient number of our cohort. Our data are supported by various studies which showed that surgery is an important element for gaining remission status leading to prolonged survival 11 12 20 . In addition, recent reports demonstrated that re-irradiation even in unfavorable sites can achieve remission in a significantly higher percentage of patients compared to those without radiotherapy 10 21 22 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the difference did not reach statistical significance, which may be due to the small patient number of our cohort. Our data are supported by various studies which showed that surgery is an important element for gaining remission status leading to prolonged survival 11 12 20 . In addition, recent reports demonstrated that re-irradiation even in unfavorable sites can achieve remission in a significantly higher percentage of patients compared to those without radiotherapy 10 21 22 .…”
Section: Discussionsupporting
confidence: 87%
“…Whereas large clinical trials assessing treatment strategies for de novo disease included several hundred patients [3,4], therapeutic concepts for relapsed patients are not well established. Intensive chemotherapeutic regimens using topotecan, carboplatin, cyclophosphamide and etoposide (TECC) or regimens including anthracyclines (e. g. ACCTIVE) [5,6] or vincristine, irinotecan and temozolomide such as the new European standard protocol for STS relapse [7] demonstrated some efficacy in limited numbers of patients to date, and local tumor control by surgery, radiation [8][9][10] or the combination of both [11,12] seems to play a role in improving overall survival. In addition, according to preliminary data, it was hoped that the use of novel compounds which inhibit specific molecular tumor targets ("targeted therapy"), such as PARP/ MEK/HDAC/TK inhibitors improves outcome [13,14] and relapse studies on individualized treatment approaches based on genetic tumor alterations might play a more important role in future [20].…”
Section: Introductionmentioning
confidence: 99%
“…In H&N RMS, parameningeal locations are associated with poor prognosis due to a variety of reasons, including relatively delayed clinical presentation (e.g., orbital locations become symptomatic earlier due to visual problems or proptosis) and the proximity to the skull base, nerves and vessels, that can preclude radical surgical excision [2,14,15]. Different biological behavior of parameningeal RMS has also been proposed [2].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative morbidity has also been reduced-thanks to the development of combined minimally invasive endoscopic and transcranial or transfacial approaches and free-flap reconstructive possibilities, which limit functional and cosmetic sequelae (34)(35)(36). In the retrospective study of 92 HN-RMS (both ERMS and ARMS) by Dombrowski et al (16), surgery was associated with a reduced risk of mortality after adjusting for TNM staging and location of the tumor (p = 0.05). Furthermore, in our series, the quality of the resection assessed by the resection margins (R0, R1, or R2) was not correlated with OS and EFS.…”
Section: Survival and Prognostic Factorsmentioning
confidence: 99%
“…About half of the patients treated for localized ARMS undergo a relapse (14). The 5-year overall survival (OS) of patients with head and neck ARMS (HN-ARMS) ranges from 35% (15) to 80% (16). To evaluate the prognosis value of clinical and pathological features and the impact on outcome of LN staging and locoregional therapies, we reviewed all patients <21 years with localized ARMS treated in France in the prospective EpSSG RMS 2005 study.…”
Section: Introductionmentioning
confidence: 99%